The Evolution of the Romanian Capital Market – Limits and Performances - Gabriela Anghelache (Theoretical and Applied Economics, 2006)
In this paper, there are described issues regarding the capital market evolution, focusing on the last year’s results and the current year’s perspectives. The evolutions for the Bucharest Stock Exchange, the RASDAQ Electronic Stock Exchange and the Sibiu Monetary-Financial and Commodities Exchange are analyzed. There are also presented aspects regarding the mutual funds – FDI and the direct foreign investments in the Romanian market.